Overview Policies, Problems and Prospects of Higher Education in India - Dr. Vinod Kumar (Journal of Advanced Research in Education, 2024)
Indian education system traditionally served a particular segment of the society belonging to selected groups and elites. Colonial rule under the British Government developed concept of a modern state, modern economy and modern education system. After Independence, Jawaharlal Nehru visualized India as a secular democratic state. School curriculum was based on twin themes of inclusiveness and national pride, ensuring that India’s different communities could live together peacefully as one nation. Higher education through institutions like IITs and IIMs formed a major contribution to the Nehruvian vision of a selfreliant and modern India. Drawing on Nehru’s vision and articulating most of his themes, the Kothari Commission was set up in 1964 to formulate a coherent education policy for India. Kothari Commission felt education is meant to improve productivities, promote national and social harmony, consolidate democracy, modernize the country and develop social, moral and spiritual values. Attainment of this objective is possible only through the education policy which would provide free and compulsory education to all children up to the age of 14. According to Kothari Commission, Education policy must feature development of languages, equality of educational opportunities to all social groups and development and prioritization of scientific education and research. The Commission also lay emphasis on the removal of illiteracy and provision of adult education. The theme of the present paper is Policies, Problems and Prospects of Higher Education in India. The main objective of the present paper is to be analyze the policies, problems and prospects of Higher Education in India.